Improving the quality of distance learning during the covid-19 pandemic through academic supervision for teachers in man 2 maluku tengah - Harman Muh Ali (Balai Diklat Keagamaan Ambon, 2022)
This study aims to find out whether carrying out academic supervision, can improve the quality of the online learning process and to find out the mechanism for implementing academic supervision in the online learning process during the CoronaVirus Disease (Covid-19) pandemic in the odd semester of the 2020/2021 academic year. This research is descriptive qualitative research with the subjects studied being 23 civil servant teachers at MAN 2 Central Maluku. The technique collects data using observation, interviews, and documentation. The online learning system is a new thing for teachers and students of MAN 2 Central Maluku because it greatly affects the quality of the learning process. Madrasah heads must take appropriate steps to overcome the problems faced by teachers when online learning is carried out. Therefore, the head of the madrasah as a supervisor carries out academic supervision with an implementation mechanism, teachers teach using laptop media or computers connected to projector while students learn from home each using Android cell phones (HP).